Mucus of Achatina fulica stimulates mineralization and inflammatory response in dental pulp cells - Fahsai Kantawong (2018)
© TÜBİTAK. Dental pulp tissue contains stem cells that can be isolated and used for regenerative medicine in tooth restoration or autologous transplantation. The aim of this study was to observe the mineralization and gene expression in dental pulp cells (DPCs) following treatment with snail mucus. Snail mucus was collected from adult Achatina fulica and processed as a dry powder by the freeze-drying technique. The mucus powder was dissolved in a culture medium at a concentration of 15 μg/mL. DPCs were prepared by the outgrowth technique and cultured in a 6-well plate at a density of 5 × 104cells per well. A mucus-supplemented medium (15 μg/mL) was added to each well. Cell culture was maintained for 3 weeks. The results of Alizarin Red S staining indicated that the DPCs cultured in a medium supplemented with snail mucus showed a higher number of mineralized nodules as compared with the control group cultured in a normal medium. The increased expression of osteopontin and NF-κB reflected the differentiation process of DPCs into bone cells. Snail mucus also induced the expression of some inflammatory genes in DPCs. The results demonstrated that snail mucus has the potential to be used in regenerating and repairing bone and teeth.